2014
DOI: 10.1130/g35245.1
|View full text |Cite
|
Sign up to set email alerts
|

Late Holocene fluctuations of Qori Kalis outlet glacier, Quelccaya Ice Cap, Peruvian Andes

Abstract: The temporal and spatial patterns of late Holocene climate conditions provide valuable information for testing hypothesized mechanisms of recent climate changes. As a proxy for late Holocene climate in the southern tropics, we present a 10 Be chronology of moraines deposited by Qori Kalis, an outlet glacier of Quelccaya Ice Cap in Peru. The Qori Kalis moraines are located downfl ow from the Quelccaya ice cores and provide the fi rst glacial extent record that can be compared directly to annually resolved tropi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 37 publications
(42 reference statements)
5
49
0
Order By: Relevance
“…A pioneering study by Schaefer et al (2009) showed that the age range of 10 Be dating can be expanded to ages as young as 130 years due to the increasing sensitivity of measurements for glaciers in the Southern Alps, New Zealand. Recently, successful applications of cosmogenic nuclide dating on LIA moraines have also been reported for other regions, such as the European Alps (Schimmelpfennig et al, 2014) and the Peruvian Andes (Stroup et al, 2014). However, the high-energy environments of glaciers in the eastern Nyainqêntanglha Range pose great challenges to the application of this method, particularly regarding prior or incomplete exposure (cf.…”
Section: Dating Methodsmentioning
confidence: 96%
“…A pioneering study by Schaefer et al (2009) showed that the age range of 10 Be dating can be expanded to ages as young as 130 years due to the increasing sensitivity of measurements for glaciers in the Southern Alps, New Zealand. Recently, successful applications of cosmogenic nuclide dating on LIA moraines have also been reported for other regions, such as the European Alps (Schimmelpfennig et al, 2014) and the Peruvian Andes (Stroup et al, 2014). However, the high-energy environments of glaciers in the eastern Nyainqêntanglha Range pose great challenges to the application of this method, particularly regarding prior or incomplete exposure (cf.…”
Section: Dating Methodsmentioning
confidence: 96%
“…It is possible that NC9 and NC10 are dating 1-2 older advances and NCNE01 a younger advance, which reached the same place and added a new moraine to pre-existing moraines. The younger moraines aggregation on older moraines, could also be the cause of the dispersed ages in many Andean glacial sites, such as Cajamarca [45], Cordillera Blanca [29], Jeulla Raju [105], Huayhuash [106], Junín [28], Quelccaya ice cap [6,107], Carabaya [46], Huayna Potosí, Río Suturi and Huamaní Loma [39]; Coropuna [37,38]; (this work); Hualca Hualca [7], Cerro Tunupa [8], and Uturuncu volcano [9].…”
Section: The Glaciers Maximum Extension and The Polygenic Moraines Dementioning
confidence: 93%
“…1], sits atop an ignimbrite plateau (Audebaud, 1973;Chavez et al, 1997) with multiple valleys connecting the plateau to the surrounding landscape that contain glacial features (Mercer et al, 1975;Mercer and Palacios, 1977;Goodman et al, 2001;Mark et al, 2002;Kelly et al, 2012;Stroup et al, 2014;Kelly et al, 2015). The Rio Huancan e valley, on the southwest side of the QIC (Fig.…”
Section: Study Sitementioning
confidence: 97%
“…First, the climate drivers of tropical glacier length changes are poorly understood. The relative importance of temperature versus precipitation rate changes on tropical glacier length changes is debated (Kaser et al, 2004;Taylor et al, 2006;Thompson et al, 2006;Vuille et al, 2008;Licciardi et al, 2009;Jomelli et al, 2011;Thompson et al, 2013;Stroup et al, 2014;Jomelli et al, 2014). Second, the climate interpretation of glacial geomorphic features is not fully understood.…”
Section: Introductionmentioning
confidence: 98%